Investigating the structural performance of graphene nanoparticles infused reinforced concrete - Hilal Khan; Zamil Bin Zahid (Discover Civil Engineering)
Abstract This research investigates the structural performance of reinforced concrete infused with graphene nanoplatelets (GNPs). To address the urgent need to reduce the carbon footprint of the construction industry, this study explores the potential of GNPs to enhance concrete properties, thereby decreasing the required cement quantity. Various GNP concentrations were incorporated into concrete mixes, followed by thorough testing of their mechanical and microstructural properties. Experimental results revealed significant improvements, such as compressive strength increased by up to 40%, tensile strength by 27%, and toughness by 47%. Furthermore, the incorporation of GNPs demonstrated potential CO₂ reductions of up to 446 kg per ton of cement, contributing to sustainable construction practices. SEM analysis showed improved microstructure with fewer voids and enhanced crystallinity. Additionally, GNP-reinforced concrete exhibited higher electrical resistivity and pulse velocity, indicating sound durability and reduced porosity. These findings underscore the effectiveness of GNPs in creating more tough, durable, and environmentally sustainable concrete composites.